PASAR RAKYAT YANG MEMPENGARUHI KINERJA JALAN SETELAH PEKERJAAN PENGGANTIAN JEMBATAN RUAS JALAN - Ranty - Christiana; Irvhaneil Irvhaneil; Syarifah Melly Maulina (LPPM Universitas Abdurrab, 2023)
Puring market is located on riverside of the Kapuas river that operates 24 hours. The Ministry of Public Works and Public Housing in 2020 carried out the work to replace khatulistiwa road (Pontianak) and the completion of the work in 2021 was at the Puring market location, when the bridge work was carried out it was certain that there would be quite a high vehicle delay. It is necessary to review the side friction and road performance due to the Puring market activity after the bridge replacement work has been completed. The method used for this research is a descriptive quantitative method with data collection to determine side friction and road performance. Calculations will be made based on the Indonesian Road Capacity Manual (MKJI). The results of the research show that road performance is close to saturation with the resulting value of DS = 0.74. This provides evidence that there is an impact by these market activities on the performance of the Pontianak Katulistiwa road after the operation of the new bridge. The side barrier survey indicates that the area is included in a commercial area with very high roadside activity.